Riparian tree and bird diversity in Cisadane River, South Tangerang City, Indonesia - URFI IZZATI; HAYATI SARI HASIBUAN (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Izzati U, Hasibuan HS. 2019. Riparian tree and bird diversity in Cisadane River, South Tangerang City, Indonesia. Biodiversitas 20: 595-603. Riparian is a riverbank area that has unique characteristics. It is a combination of terrestrial with aquatic habitats so that riparian ecosystems have high biodiversity values. Riparian is included in a protected area that is naturally designated for vegetation, but in reality, riparian areas, especially in urban areas, have a lot of conversion of land functions by humans so that it can disrupt diversity of tree and bird species. This study aims to identify the diversity of tree and bird species and the correlation between the two. Riparian length of Cisadane River, South Tangerang City is 20.15 km. The method used was plot line with size of 20 m x 20 m for tree data and line transect for bird data by systematic sampling with a random start then analyzed using Shannon Wiener index. The results obtained were found 22 tree species included in 11 families with species diversity index (H') of 2.707 and 40 bird species belonging to 25 families with species diversity index (H') of 2.794. The diversity of tree and bird species is classified as medium. The results of the analysis using the Pearson correlation between the diversity of tree with bird species obtained that there was no relationship between the two. Based on these results, riparian zones in urban areas need to be maintained and improved in quality so that the diversity of tree and bird species increases so as to create a stable ecosystem.